ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI JOB SATISFACTION AUDITOR YANG BEKERJA PADA KANTOR AKUNTAN PUBLIK DI JAKARTA - Rando Meidiansyah Putra; Herry Laksito (Diponegoro Journal of Accounting, 2012)
This study aims to examine the factors - factors that affect job satisfaction, the auditor who worked on KAP in Jakrta. The unit of analysis of this study is the auditor who worked on the public accounting firm in Jakarta. The number of samples is 120 auditors and the data processed using SPSS. The analysis performed included tests of validity, test reliability, test classic assumptions, multiple linear regression analysis including the F test, t test, and coefficient of determination. The results of the analysis of the study can be seen that the variable consideran leadership style, structure leadership style, and complexity of the task has a positive effect on job satisfaction. While the variable of time budget pressures have a negative influence on job satisfaction.